PERAMALAN PERMINTAAN DENGAN PENDEKATAN TIME SERIES DAN PERENCANAAN PRODUKSI AGREGAT - Wijayanti, Erik; Rosydi, Khafidz (Department of Industrial Engineering - Universitas Yudharta Pasuruan, 2019)
The problem being faced is the product demand that is not constant, so that production planning becomes difficult. The result is often the difference between the amount of demand and product inventory. The company must find an effective and efficient production planning strategy in meeting fluctuating demands. This research is conducted demand forecasting with the help of Minitab software 18. The best forecasting results are then used as production targets. Aggregate production planning is implemented using hybrid and transportation methods to meet predicted demand by adjusting existing resources including regular working hours, overtime work hours and addition of production lines. The results obtained that the best forecasting using the double exponential smoothing method with a coefficient of 0.1. Hybrid aggregate production methods and transportation provide the same costs, while for orders of material requirements (lotting) the POQ method results in a smaller EOQ cost.